2022
DOI: 10.1002/jmv.27927
|View full text |Cite
|
Sign up to set email alerts
|

Omicron (BA.1) and sub‐variants (BA.1.1, BA.2, and BA.3) of SARS‐CoV‐2 spike infectivity and pathogenicity: A comparative sequence and structural‐based computational assessment

Abstract: The Omicron variant of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has now spread throughout the world. We used computational tools to assess the spike infectivity, transmission, and pathogenicity of Omicron (BA.1) and sub‐variants (BA.1.1, BA.2, and BA.3) in this study. BA.1 has 39 mutations, BA.1.1 has 40 mutations, BA.2 has 31 mutations, and BA.3 has 34 mutations, with 21 shared mutations between all. We observed 11 common mutations in Omicron's receptor‐binding domain (RBD) and sub‐var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 54 publications
(81 reference statements)
6
138
0
Order By: Relevance
“…( Abrusán and Marsh, 2016 , Ao et al, 2021 , Banoun, 2021 , Basky and Vogel, 2022 , Bekliz et al, 2022 , Bonilla-Aldana and Rodriguez-Morales, 2021 , Burki, , Callaway, 2021 , Cao et al, 2021 , Centers for Disease Control and Prevention, 2021 , Clemens et al, 2022 , Cohen et al, 2022 , Cookson and Barnes, 2021 , COVID and Team, 2021 , Dejnirattisai et al, 2022 , Dev and Sengupta, 2020 , Devlin and Kollewe, 2021 , Dikdan et al, 2022 , Dubey et al, 2022 , European Centre for Disease Prevention and Control (ECDC), 2021 , Fabricius et al, 2021 , Gardner and Kilpatrick, 2021 , GeurtsvanKessel et al, 2022 , Gu et al, 2022 , Guihot et al, 2020 , Hanage, 2021 , Hodcroft, 2021 , Hurst, 2021 , Iqbal, 2020 , Islam and Hossain, 2022 , John, 2022 , Kaplonek et al, 2021 , Kaushik, 2021 , Kumar et al, 2022 , Lapid, 2021 , Le Page, 2021 , Lee et al, 2022 , Lu et al, 2020 , Mahase, 2021b , Mehta, 2020 , Melinda, 2022 , Mohapatra et al, 2022 , Mohapatra et al, 2022 , Mostafavi et al, 2022 , Mujawar et al, 2020 , Omicron, , P´erez-Then et al, 2022 , Paliwal et al, 2020 , Patalon et al, 2022 , Penner, 2021 , Phan et al, 2022 , Planas et al, 2021 , Planas et al, 2022 , Rahimi and Abadi, 2022 , Rathinasamy and Kandhasamy, 2022 , Tanne, 2021 , …”
Section: Uncited Referencesmentioning
confidence: 99%
“…( Abrusán and Marsh, 2016 , Ao et al, 2021 , Banoun, 2021 , Basky and Vogel, 2022 , Bekliz et al, 2022 , Bonilla-Aldana and Rodriguez-Morales, 2021 , Burki, , Callaway, 2021 , Cao et al, 2021 , Centers for Disease Control and Prevention, 2021 , Clemens et al, 2022 , Cohen et al, 2022 , Cookson and Barnes, 2021 , COVID and Team, 2021 , Dejnirattisai et al, 2022 , Dev and Sengupta, 2020 , Devlin and Kollewe, 2021 , Dikdan et al, 2022 , Dubey et al, 2022 , European Centre for Disease Prevention and Control (ECDC), 2021 , Fabricius et al, 2021 , Gardner and Kilpatrick, 2021 , GeurtsvanKessel et al, 2022 , Gu et al, 2022 , Guihot et al, 2020 , Hanage, 2021 , Hodcroft, 2021 , Hurst, 2021 , Iqbal, 2020 , Islam and Hossain, 2022 , John, 2022 , Kaplonek et al, 2021 , Kaushik, 2021 , Kumar et al, 2022 , Lapid, 2021 , Le Page, 2021 , Lee et al, 2022 , Lu et al, 2020 , Mahase, 2021b , Mehta, 2020 , Melinda, 2022 , Mohapatra et al, 2022 , Mohapatra et al, 2022 , Mostafavi et al, 2022 , Mujawar et al, 2020 , Omicron, , P´erez-Then et al, 2022 , Paliwal et al, 2020 , Patalon et al, 2022 , Penner, 2021 , Phan et al, 2022 , Planas et al, 2021 , Planas et al, 2022 , Rahimi and Abadi, 2022 , Rathinasamy and Kandhasamy, 2022 , Tanne, 2021 , …”
Section: Uncited Referencesmentioning
confidence: 99%
“…Furthermore, the deletion in the amino acid positions 24-26 and four substitutions in the RBD (S371F, T376A, D405N, and R408S), located in the strategical antigenic site, raise a concern about the possible ineffectiveness of the currently available neutralizing monoclonal antibodies [12,13]. RBD-ACE2 docking under revision studies suggests that all Omicron variants (BA.1, BA.1.1, BA.2, and BA.3) have a greater affinity for the ACE2 receptor because several mutations increase the number of salt bridges and hydrogen bonds between the receptor-binding domain (RBD) and its electronegative receptor (ACE2) [14]. Consequently, antigenic cartography analysis performed to quantify and visualize the antigenic differences between SARS-CoV-2 VOCs have revealed that the BA.2 lineage is qualitatively unique [15].…”
Section: Virology and Mutational Profilementioning
confidence: 99%
“…Meanwhile several Omicron lineages have been found: BA.1/B.1.1.529.1, BA.1.1/B.1.1.529.1.1, BA.2/B.1.1.529.2 and BA.3/B.1.1.529.3. Omicron and its subvariant are characterized by a milder course, but higher infectivity due to the high number of more than 30 amino acid mutations within the spike protein, 15 of which occur in the receptor-binding domain (RBD; [ 2 ]). These mutations seem to be associated a higher positive electrostatic surface potential increasing the interaction between RBD and electronegative human angiotensin-converting enzyme 2 [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Omicron and its subvariant are characterized by a milder course, but higher infectivity due to the high number of more than 30 amino acid mutations within the spike protein, 15 of which occur in the receptor-binding domain (RBD; [ 2 ]). These mutations seem to be associated a higher positive electrostatic surface potential increasing the interaction between RBD and electronegative human angiotensin-converting enzyme 2 [ 2 ]. Consequently, Omicron rapidly spread in regions with high levels of population immunity and has now emerged as the dominant strain in the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%